LOCUS OF CONTROL AND RESPONSIBILITY FOR EMPLOYEE PERFORMANCE - Hilma Harmen; Agus Rahmadsyah; Aprinawati (LPPM STIE EKA PRASETYA, 2022)
This article analyzes the influence of locus of control and responsibility on the performance of the employees of the Regional Water Company (PDAM) Tirtanadi, Tuasan Medan Branch. The sample consisted of eighty respondents, namely all company employees from various work units using proportional random sampling technique. Data was collected by distributing questionnaires to respondents and then processed using multiple regression analysis. It was found that locus of control has an effect on employee performance, on the other hand not with responsibility. Simultaneously locus of control and responsibility affect employee job satisfaction. To improve the performance of the employees of PDAM Tirtanadi, Tuasan Medan, several suggestions are given in this article.